P‐11.12: Analysis of the LC aligntment and performance at specific pixel design. (4th October 2019) - Ren, Wei; Song, Yan-Jun; Zhao, Yong-Chao; Chen, Jie; Hsieh, Chung-Ching; Chiu, Chung-Yi
Abstract : In this paper, we analysis the influence about the alignment of liquid crystal display using the DBS(data BM less) design and BM structrue has investigated. Because DBS design have constract ratio less than normal design. As a result, in oder to improve the CR, the DBS and BM design simultaneous applicated. However, this new design have some LC alignment issue, we study the LC alignment and performance effect of the liquid crystal include DBScom potential, voltage, and BM on the set of locations ; in this way, promotion the production of quality and process stability